Aortopulmonary Fistula after Multiple Pulmonary Artery Stenting and Dilatation for Postarterial Switch Supravalvular Stenosis - Maude Pagé; Oana Nastase; Frédéric Maes; Joëlle Kefer; Thierry Sluysmans; Alain Poncelet; Jean Rubay; Agnès Pasquet (Case Reports in Cardiology)
We present a case of iatrogenic aortopulmonary fistula following pulmonary artery (PA) stenting late after arterial switch operation (ASO) for D-transposition of the great arteries (D-TGA), an unusual complication that may be encountered more frequently in contemporary adult cardiology clinics. The diagnosis should be sought in the face of unexplained heart failure in patients who underwent ASO and subsequent PA angioplasty. Treatment should be instituted in a timely fashion, and options include surgical correction or implantation of a duct occluder or covered stent.